2014
DOI: 10.1515/zpch-2013-0452
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior of Carbamazepine

Abstract: Carbamazepine (CBZ) is known for its variety of anhydrous and hydrous polymorphs. Herein, a thorough analysis of the crystallization behavior of CBZ is presented. The influence of the solvent and the concentration on the crystallization behavior under different environmental conditions is investigated by combined in situ XRD and Raman spectroscopy measurements. Crystallization studies conducted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…16,17 The type of acoustically levitation experiments highlighted here essentially relied on the monitorization of the droplet chemical composition, the droplet size, and the phases detected, as crystallization progresses. [16][17][18]28 The influence of surface cooling and the possible capture of atmospheric water by the droplet as the solvent evaporates have remained two unexplored issues. Previous experiments carried out with pure organic solvents suggest, however, that both these effects may be significant in an evaporative crystallization process.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 The type of acoustically levitation experiments highlighted here essentially relied on the monitorization of the droplet chemical composition, the droplet size, and the phases detected, as crystallization progresses. [16][17][18]28 The influence of surface cooling and the possible capture of atmospheric water by the droplet as the solvent evaporates have remained two unexplored issues. Previous experiments carried out with pure organic solvents suggest, however, that both these effects may be significant in an evaporative crystallization process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies on acoustically levitated droplets with simultaneous real-time analysis using different techniques (synchrotron X-ray diffraction, Raman spectroscopy, and imaging) were also performed to investigate crystallization in a contactless environment and to identify intermediate stages preceding the final product. A judicious choice of solvent enabled, for example, the selective isolation of metastable crystalline forms of ROY, 5-methyl-2-[(2-nitrophenyl)­amino]-3-thiophenecarbonitrile . ROY is famous for its numerous colorful crystalline modifications that can be isolated in walled vessels. Experiments with paracetamol showed that not only the container surface-free conditions, but specially the use of a specific solvent and the saturation degree during crystallization from solution, triggers and controls the selective formation of the thermodynamically stable form I and the metastable form II .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further advantage of the contact-less sample environment offered by ultrasonic levitation is the ready application of different analytical techniques. It has been combined with methods such as FTIR, Raman spectroscopy, and microscopy as well as UV–visible spectroscopy. There are few examples of the coupling of ultrasonic levitation with small-angle X-ray scattering (SAXS); it has been applied to the study of the growth mechanism of inorganic and organic crystals, , the agglomeration of soluble proteins, and the structures of glassy materials . It is reasonably straightforward to combine several techniques with ultrasonic levitation to analyze the same sample simultaneously.…”
mentioning
confidence: 99%
“…To access these levels of supersaturation any container walls which might act as heterogeneous nucleation sites have to be circumvented. In the past few years, acoustic levitators generating an ultrasonic standing wave for the containerless levitation of objects, such as droplets or solid samples, have gained considerable interest to study crystallization processes [15][16][17][18][19][20][21][22][23][24][25][26]. We briefly describe the experimental development up to the introduction of a climate unit for the control of the chemical potential of the surrounding vapor phase [27].…”
Section: Introductionmentioning
confidence: 99%